Kinetic Studies On Carboxylesterase Of Model Nematode Caenorhabditis Elegans Exposed In Vitro To Dichlorvos (Applied Biological Research, 2015)
The study was aimed to understand the kinetics of organophosphorus  detoxifying enzyme carboxylesterase (EC 3.1.1.1) and to know the its  sensitivity in Caenorhabditis elegans, a moist soil dwelling nematode  used as model system for studying xenobiotics. Enzymatic hydrolysis of  ρ-nitrophenylacetate (PNPA) showed a Km value of 20.95 μM, Vmax of  4.62 nmol min-1 mg-1 protein and substrate saturation of 350 μM for  carboxylesterase (CaE) in vitro kinetics on exposure to dichlorvos from  elegans. The IC50 with dichlorvos, an organophosphorus compound, was 81.16 nm at excess of Km. LB plot showed the Km, Vmax and Vmax/Km  values of inhibited CaE: 19.57 µM, 2.88 nmol min-1 mg-1 protein and 0.14 min-1 mg-1 protein, respectively, at IC50 concentration of dichlorvos. Inverse LB plot revealed the inhibition of CaE in C. elegans irreversible in presence of dichlorvos. Hence this may be used as invertebrate
Keywords: Caenorhabditis elegans; carboxylesterase; kinetics; dichlorvos and Lineweaver-Burk plot